Iron controls T helper cell pathogenicity by promoting glucose metabolism in autoimmune myopathy. Issue 8 (2nd August 2022) - Lai, Yimei; Zhao, Siyuan; Chen, Binfeng; Huang, Yuefang; Guo, Chaohuan; Li, Mengyuan; Ye, Baokui; Wang, Shuyi; Zhang, Hui; Yang, Niansheng
Abstract: Background: T helper cells in patients with autoimmune disease of idiopathic inflammatory myopathies (IIM) are characterized with the proinflammatory phenotypes. The underlying mechanisms remain unknown. Methods: RNA sequencing was performed for differential expression genes. Gene expression in CD4 + T‐cells was confirmed by quantitative real‐time PCR. CD4 + T‐cells from IIM patients or healthy controls were evaluated for metabolic activities by Seahorse assay. Glucose uptake, T‐cell proliferation and differentiation were evaluated and measured by flow cytometry. Human CD4 + T‐cells treated with iron chelators or Pfkfb4 siRNA were measured for glucose metabolism, proliferation and differentiation. Signalling pathway activation was evaluated by western blot and flow cytometry. Mouse model of experimental autoimmune myositis (EAM) were induced and treated with iron chelator or rapamycin. CD4 + T‐cell differentiation and muscle inflammation in the EAM mice were evaluated. Results: RNA‐sequencing analysis revealed that iron was involved with glucose metabolism and CD4 + T‐cell differentiation. IIM patient‐derived CD4 + T‐cells showed enhanced glycolysis and mitochondrial respiration, which was inhibited by iron chelation. CD4 + T‐cells from patients with IIM was proinflammatory and iron chelation suppressed the differentiation of interferon gamma (IFNγ)‐ and interleukin (IL)‐17A‐producing CD4 + T‐cells, which resulted in an increased percentage of regulatory T (Treg) cells. Mechanistically, iron promoted glucose metabolism by an upregulation of PFKFB4 through AKT‐mTOR signalling pathway. Notably, the knockdown of Pfkfb4 decreased glucose influx and thus suppressed the differentiation of IFNγ‐ and IL‐17A‐producing CD4 + T‐cells. In vivo, iron chelation inhibited mTOR signalling pathway and reduced PFKFB4 expression in CD4 + T‐cells, resulting in reduced proinflammatory IFNγ‐ and IL‐17A‐producing CD4 + T‐cells and increased Foxp3 + Treg cells, leading to ameliorated muscle inflammation. Conclusions: Iron directs CD4 + T‐cells into a proinflammatory phenotype by enhancing glucose metabolism. Therapeutic targeting of iron metabolism should have the potential to normalize glucose metabolism in CD4 + T‐cells and reverse their proinflammatory phenotype in IIM. Abstract : Glucose metabolism is enhanced in CD4 + T‐cells from IIM patients; Iron promotes the differentiation of proinflammatory CD4 + T‐cells; Iron enhances glucose metabolism in CD4 + T‐cells by upregulating PFKFB4 through AKT‐mTOR signaling; Iron chelation inhibits autoreactive T‐cell response and prevents autoimmune myositis.